Survey of new refugees, 2005-2009 (UK Data Service, 2010)
The Analysis, Research and Knowledge Management section (ARK) within the UK Border Agency commissioned the Survey of New Refugees to provide a longitudinal study of refugee integration in the UK. The overall aim of the survey was two-fold: (i) to collect information on the characteristics of new refugees at the time of their asylum decision; and (ii) to provide data on the integration of new refugees in the UK over time. A postal baseline questionnaire was sent to all new refugees who were granted a positive decision of asylum, humanitarian protection or discretionary leave to remain between 1 December 2005 and 25 March 2007. Three follow-up questionnaires were issued 8, 15 and 21 months later. The baseline questionnaire collected information on the characteristics of refugees at the time of their asylum decision, including their previous education and employment, English language ability, physical and emotional health, and their social support and service needs. Three follow-up questionnaires were used to collect information on how these refugees integrated in the UK over 21 months. Integration was considered in terms of the English language skills, employment and housing of new refugees, and how these changed over time. Over 900 refugees provided information at all four sweeps. The findings of this research have been published in two Home Office Research Reports (Nos. 36 and 37) and one Summary Report (No.35), all included in the study documentation. A further Research Report (No.43), The Migrant Journey, is also available (see Publications section for references and links).